Open and Distance Learning Research Agenda for the 21st Century: The Shift from Seller's Market to Buyer's Market in Open and Distance Learning (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Consumerism, quality and innovation, are to dominate in this millennium, thanks to the economic reforms ushered in developed and developing Nations and the several agreements signed under the World Trade Organisation. The transition will be from a predominantly ‘Seller’s Market' to a 'Buyers’ Market' where the choice exercised by the consumerism. We mean the process of realizing the rights of the right learning as envisaged in Open and Distance Learning”.